Preclinical assessment of the immunosuppressive properties of an anti-CD4 monoclonal antibody (MAB) in an allogeneic foetal rat pancreatic transplantation model - Muller, Christo John Frederick (Stellenbosch : Stellenbosch University, 2012)
Dissertation (PhD)--Stellenbosch University, 2004.